Endometrial Thickness Measured by Ultrasonography in Postmenopausal Patients With Endometrial Carcinoma Has Significance, Irrespective of Histological Subtype. Issue 7 (1st September 2013) - Hosoi, Ayako; Ueda, Yutaka; Shindo, Mariko; Nakagawa, Satoshi; Matsuzaki, Shinya; Kobayashi, Eiji; Kimura, Toshihiro; Yoshino, Kiyoshi; Fujita, Masami; Kimura, Tadashi
Abstract : Objective: The criterion standard of practice for gynecologists is to measure the endometrial thickness with ultrasonography in women presenting with postmenopausal bleeding. A recent study reported that a thin endometrial stripe upon ultrasonography did not reliably exclude type II endometrial carcinoma. The aim of the present study was to reevaluate the reliability of ultrasonographic measurement of the endometrium for prediction of endometrial carcinomas of both types I and II in postmenopausal women. Methods: We collected clinical data from patients with endometrial carcinoma who underwent surgical treatment at the Department of Obstetrics and Gynecology of the Osaka University Hospital, Osaka, Japan, during our study period from 2010 to 2012. Only the postmenopausal cases were included in our study. We excluded cases with insufficient clinical data. Results: Preoperative measurement of the endometrium by transvaginal ultrasonography revealed that the endometrium was greater than 4 mm in 80 (89%) of the 90 type I cases and in 41 (93%) of the 44 type II cases. The median of the endometrial thickness measured with transvaginal ultrasonography preoperatively in type I cases, including both patients with myometrial invasion less than 1/2 and those with myometrial invasion greater than 1/2, was 13 mm (range, 1–78 mm). That of type II cases was 15 mm (range, 1–54 mm). This difference was not statistically significant ( P = 0.46 by Mann-Whitney U test). These results implied that endometrial thickness was not significantly associated with the type of tumors. Conclusions: Ultrasonographic measurements of the endometrium for prediction of endometrial carcinomas in postmenopausal women are reliable for both type I and type II tumors. These results encourage us to continue to use the "4-mm (5-mm) rule" to evaluate endometrial thickness in postmenopausal women, in opposition to a previous report.